Effect of guar and arabic gums on qualitative properties of extruded rice. (17th January 2019) - Saadat, Saba; Movahhed, Sara; Ahmadi Chenarbon, Hossein
Abstract: The rice milling process is carried out extensively to alter its texture and whiteness, increase its bonding with water, improve its digestibility, and reduce its cooking time. Broken rice grains followed by lower rice efficiency during processing and milling of rice paddy are a major challenge contributing to the reduced economic productivity. Moreover, separation of rice bran also reduces its nutritional value. Accordingly, the extrusion process in turning flour from broken rice into whole rice grains and its fortification can improve the economic value and nutrition value by adding mineral or vitamin in the production process. In this regard, the individual and collective effects of guar and arabic gums (0.5 and 1%) were analyzed to produce extruded rice samples ( var . Hashemi) with qualitative and organoleptic properties similar to those of the control samples. According to the results of the tests conducted before and after cooking, guar and arabic gums increased moisture content, ash, color difference, texture hardness, water uptake, solubility, lateral expansion, and cohesiveness, and reduced density, cooking loss, chewiness of the samples compared to the control samples. According to the results from before and after cooking, the treatment containing 1% guar +1% arabic was selected as the best treatment. Practical applications: The main objective of extrusion is to develop the diversity in daily foods through products with different shape, texture, colors and flavor and reduction in losses during the rice production and preparation processes as well as the improvement of qualitative and organoleptic properties of extruded rice. Advantages of the extrusion process include diversity in foods, reduce of food losses (e.g., converting broken rice into textured rice), fortification of product and the possibility of automating the process.